Career Plateau and Employee Outcomes: Evidence on Job Satisfaction, Performance, and Organizational Citizenship Behavior - Kabul Wahyu Utomo; Faizul Mubarok; Muhammad Iqbal Arrasyid (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study investigates the impact of career plateau (CP) on job satisfaction (KK), employee performance (KP), and Organizational Citizenship Behavior (OCB) among higher education support staff. Additionally, it examines whether job satisfaction and OCB serve as mediators in these relationships.Methodology: The study utilized a quantitative approach, employing Structural Equation Modeling with Partial Least Squares (SEM-PLS). Data were collected through questionnaires administered to 200 higher education staff members across multiple Indonesian institutions.Findings: The results indicate that career plateau significantly reduces job satisfaction but does not directly influence employee performance or OCB. Job satisfaction enhances OCB, which, in turn, improves employee performance. Mediation analysis reveals that career plateau affects performance indirectly through a sequential pathway involving job satisfaction and OCB.Conclusion: Career plateau primarily affects affective factors rather than directly influencing performance. Enhancing job satisfaction and fostering OCB are essential strategies to mitigate the negative consequences of career stagnation and improve staff performance in higher education.